24R-Type LPSO Microstructure of the Novel Mg-Y-Zn Alloy (Journal of Atomic and Molecular Sciences, 2013)
The microstructue of the novel long period stacking ordered (LPSO) structure in Mg-Y-Zn alloy has been systematically studied based on the density functional theory. The lattice positions of the Y and Zn atoms are determined theoretically, it is shown that the additive atoms are firstly enriched in the stacking fault layers at the two ends, a small amount are distributed in the interior stacking fault layers of the structure. And the arrangement of these Y and Zn atoms trends to be along the diagonal line of the unit cell.